A Comparison of Two Native American Navigator Formats: Face-to-Face and Telephone - Dignan, Mark B. (2005)
The study was designed to test the relative effectiveness of a Navigator intervention delivered face-to-face or by telephone to urban Native American women. The effectiveness of the intervention was evaluated using a design that included a pretest, random assignment to face-to-face or telephone group, and posttest. The Social Cognitive Theory-based intervention was a tailored education program developed to address individual risk factors for breast cancer. At posttest, self-reported mammograms in the past year increased from 29% to 41.3% in the telephone group and from 34.4%: to 45.2% in the face-to-face group. There was no difference in change from pretest to posttest between the telephone and face-to-face groups. Navigators can be effective in increasing adherence to recommendations for screening mammography among urban American Indian women.